New Zealand's food system is unsustainable : a survey of the divergent attitudes of agriculture, environment and health sector professionals towards eating guidelines : a thesis presented in partial fulfilment of the requirements for the degree of Master of Science in Nutrition and Dietetics at Massey University, Albany, New Zealand - Jones, Rebekah (Massey University, 2019)
Background: The United Nation’s (UN) Sustainable Development Goals (SDG) address the adverse health and environmental changes associated with changes in the food and nutrition system. In one of its many sustainable development initiatives, the Food and Agriculture Organisation of the UN (FAO) has called for sustainable diets, which align with SDG 2, Zero Hunger, and SDG 12, Sustainable Consumption and Production. The inclusion of sustainability characteristics in New Zealand’s (NZ) eating and activity guidelines (EAGs) would contribute to directly addressing the SDGs and lead to achieving sustainable diets. This study aimed to evaluate the agreement among sectoral professionals of including sustainability characteristics within the guidelines. Methods: Professionals within the agriculture, environment and health sectors were invited to complete an online survey to establish agreement with sustainability characteristics. Opinion and attitude questions were completed using a 5-item Likert scale. One-way ANOVA analyses were conducted to compare the level of agreement with the inclusion of sustainability statements of the three professional sector groups. A one-way ANCOVA analysis was undertaken to detect a difference in means of the sectoral levels of agreement whilst controlling for covariates. Post-hoc tests were used to determine where the significant differences in opinion lay between the sector groups. Results: Overall, 298 (65% female) respondents completed the survey from the agriculture (37%), environment (22%) and health (41%) sectors. Two-thirds (66%) of respondents were over 35 years and 90% had a tertiary education. Two-thirds (63%) of respondents disagreed with the statement that NZ’s current food system is sustainable; sector respondents from health (77%) and environment (78%) had greater disagreement than agriculture (35%) (P = 0.00). Overall, 77% of respondents agreed that sustainability characteristics should be included in guidelines; with greater agreement from health (90%) and environment (84%) versus agriculture (58%) (P = 0.00). Five sustainability characteristics received unanimously high levels of agreement (> 90%) for inclusion: dietary diversity (97%), sustainable seafood (90.8%), to limit processed foods (90.7%), reduced food waste (95.3%) and sustainable lifestyle behaviours (97.2%). Agreement for eight sustainability characteristics was higher for health and environment versus agricultural sector (P < 0.05). There was relatively lower level of agreement from all three sectors, particularly environmental (68.7%), to consume recommended serves of dairy products. Only 38.5% of all respondents agreed with the inclusion of “organic food produce”. Respondents who agreed with the inclusion of sustainability characteristics were more likely to be familiar with the EAGs and to agree NZs current food system is unsustainable. Conclusion: Professionals from the agriculture, environment and health sectors of New Zealand largely support the inclusion of sustainability characteristics within NZ’s EAGs. However, there are areas of divergence that need to be addressed for their successful development and implementation.
Appendix D: Chapter 16: Sustainable Diets was removed for copyright reasons. Jones, R., Volgliano, C., & Burlingame, B. (2019). Sustainable diets and food-based dietary guidelines. In B. Berlingame. & S. Dernini (Eds.), Sustainable diets: Linking nutrition and food systems (pp. 158-171). CAB International.
Keywords: Nutrition policy; New Zealand; Diet; Food supply; Environmental aspects; Farmers; Attitudes; Environmentalists; Medical personnel; Sustainability; food-based dietary guidelines; agriculture; environment; health; professionals